ISSUES OF FETUS DRUG SAFETY - A.V. Ostrovskaya; S.A. Sher (Union of pediatricians of Russia, 2010)
The article is focused on the issue of fetus drug safety. Development of a child's health depends both on hereditary information and environment factors. The reason for deviation from the process of normal prenatal development could be any xenobiotics, physical factors and some medications having a pathogenic effect during pregnancy on the embryo and fetus. Due to that, the physician's preventive work based on the knowledge of embryogenesis processes and critical development periods. Key words: teratogenic action, medications, prenatal development, congenital malformation, newborns, children.(Pediatric Pharmacology. - 2010; 7(1):25-28)